2020
DOI: 10.1007/s42770-020-00380-4
|View full text |Cite
|
Sign up to set email alerts
|

Host and altitude factors affect rumen bacteria in cattle

Abstract: There are many kinds of microorganisms in the gastrointestinal tract of mammals, some of which are closely related to the host. Rumen microorganisms are essential for normal physiological activities of their host by decomposing plant crude lignin and providing essential nutrients. The composition and diversity of this microbial population are influenced by the host, environment, and diet. Despite its importance, little is known about the effects of factors such as altitude variation on rumen microbial populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Another bacterial diversity study in the rumen of indigenous highland Zhongdian yellow cattle showed that Shannon indices were higher than those of rumen of lowland Jiangcheng yellow cattle. This work also reported a higher abundance of Firmicutes and Bacteroidetes, as well as enrichment for Prevotella, Butyrivibrio, and Clostridium in highland cattle rumen compared with that in low altitude cattle rumen, which was consistent with findings in other highland ruminants (Wu et al, 2020).…”
Section: Domesticated Ruminants (Yak Tibetan Sheep and Indigenous Cat...supporting
confidence: 89%
“…Another bacterial diversity study in the rumen of indigenous highland Zhongdian yellow cattle showed that Shannon indices were higher than those of rumen of lowland Jiangcheng yellow cattle. This work also reported a higher abundance of Firmicutes and Bacteroidetes, as well as enrichment for Prevotella, Butyrivibrio, and Clostridium in highland cattle rumen compared with that in low altitude cattle rumen, which was consistent with findings in other highland ruminants (Wu et al, 2020).…”
Section: Domesticated Ruminants (Yak Tibetan Sheep and Indigenous Cat...supporting
confidence: 89%
“…It has been well-proven that the rumen microbiome is related to altitude adaptation and milk performance traits. The rumen microbiome diversity of Zhongdian yak is significantly higher than that of cattle and buffalo, who live at an altitude of 1,100 m ( 7 ). Interactions of Proteobacteria-choline and Firmicutes-myristic acid in the rumen cause to changes in milk fat percentage in yaks ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, as important-fiber degrading microbes, the role of rumen fungi remains poorly understood in yak. In addition, environmental variability can strongly impact grazing studies (Wu et al, 2020), and current reports do not well-explain the role of rumen microbiota in the metabolic response to season-dependent changes in nutrient availability. Here, we explore the VFA profiles of rumen under simulated seasonal diet regiments, and characterize changes in rumen microbiota related to these seasonal diets by excluding environmental factors.…”
Section: Discussionmentioning
confidence: 83%